Exploitation and objectification of women through Video Call Sex practice in radical feminism: The study of the phenomenon in working women - Devi, Risma Auliana; Ridwan, Ahmad; Kiranantika, Anggaunita (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2025)
The exploitation and objectification of women are issues that develop across various aspects of life, including the digital realm. From a radical feminist perspective, the phenomenon of Video Call Sex arises due to the rapid advancement of digital technology, leading to increased exploitation of women. This practice commodifies women's bodies to fulfill men's sexual desires. This study aims to analyze the forms of exploitation and objectification experienced by women in Video Call Sex practices. A qualitative approach with a phenomenological perspective was used. Data collection techniques included interviews and participatory observations. The research subjects were women with direct experience in Video Call Sex who were willing to openly share their personal experiences. The study involved three informants, and data collection continued until no new information was found. The study’s findings reveal that: (1) Women are reduced to sexual objects controlled by men, either as clients or as request regulators. (2) There is a power imbalance between men and women, as women are in a vulnerable position in responding to client demands. These findings indicate that women in Video Call Sex practices face not only economic exploitation but also structural oppression that sustains gender inequality. The novelty of this research lies in its in-depth analysis of how digital technology reinforces the exploitation of women within a radical feminist framework and how this practice contributes to the expanding patriarchal system in the digital era.